Association of urinary organophosphate esters level with sex steroid hormones levels in adult males: A nationwide study, NHANES 2013–2014. (10th February 2022) - Chen, Zeyu; Qiu, Shi; Zhang, Chichen; Zhan, Yu; Liu, Liangren; Bao, Yige; Chen, Bo; Bai, Yunjin; Zheng, Xiaonan; Huang, Yin; Jin, Kun; Han, Ping; et al.
Abstract: Background: Exposure to environmental pollution via different mechanisms is associated with multiple endocrine dysfunctions. Organophosphate esters (OPEs) are endocrine‐disrupting chemicals that affect sex steroid hormones. Purpose: We aimed to study the effect of OPEs and their metabolites, such as diphenyl phosphate (DPHP), bis(1, 3‐dichloro‐2‐propyl) phosphate (BDCPP), bis(2‐chloroethyl) phosphate (BCEP), and dibutyl phosphate (DBUP), on sex steroid hormones in males. Design, setting, participants, and intervention: This cross‐sectional analytical study analyzed data from the 2013–2014 National Health and Nutrition Examination Survey among 763 male participants aged ≥20 years. Main outcome measures: The relationships between the metabolites of OPEs and total testosterone, estradiol, sex hormone‐binding globulin, and the ratio of total testosterone to estradiol (a parameter derived from total testosterone and estradiol) were evaluated using multivariate linear regression models that were adjusted for potential confounders. Results: A total of 763 participants, with a mean age of 44.59 (±15.59) years, were enrolled. Of these, 65.7% participants had non‐Hispanic white ancestry, 9.83% had non‐Hispanic black ancestry, and 15.97% had Hispanic ancestry. Participants with higher urinary level of DPHP had a lower level of total testosterone and estradiol. Moreover, higher urinary levels of BDCPP were associated with higher estradiol. Conclusion: According to our study, which is based on a representative population of US adults, exposure to OPEs was significantly associated with altered sex hormone levels (total testosterone and estradiol). Further studies focused on the underlying mechanisms regarding the association between each metabolite and sex steroid hormones are required.